FOREIGN EXPERIENCES OF USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN SMALL BUSINESS AND POSSIBILITIES OF APPLICATION IN UZBEKISTAN (Marketing Journal, 2025)
This article analyzes the foreign experience of applying artificial intelligence (AI) technologies in small businesses and explores opportunities for their implementation in Uzbekistan . The study examines best practices from the USA, Germany , South Korea , India , Israel , and other countries , highlighting possible ways of adapting them to local conditions . The paper systematically identifies key challenges in introducing AI into Uzbekistanʼs small business sector , including infrastructure limitations , shortage of skilled professionals , financial constraints , and market differences . Finally , a roadmap and policy recommendations are proposed for the effective integration of AI in small business development . 91
Keywords: artificial intelligence; small business; digital transformation; foreign experience; innovative development; adaptation; localization